Extraintestinal Crohn's disease (metastatic Crohn's disease) - Rożalski, Michał (Dermatology Review/Przegląd Dermatologiczny, 2014)
Crohn's disease (CD) is an inflammatory bowel disorder that may involve any segment of the gastrointestinal tract from the oral cavity to the anus. CD belongs to the group of nonspecific inflammatory bowel diseases of unknown etiology. Its frequency is higher in well-developed countries. Attention is paid to increasing morbidity recently, which may be due to economic growth and changing habits of nutrition. CD may also involve different organs, including the skin. Skin lesions appear in 14–44% of patients with intestinal CD. We can divide them into 3 groups: specific lesions, reactive lesions associated with CD, and nutritional skin changes. The most frequent specific skin lesions, observed in 68% of patients, are perianal fissures, fistulas, and abscesses, which are due to direct spread of the inflammation from the bowel. The other frequent skin changes are reactive skin lesions such as erythema nodosum (8% of patients), pyoderma gangrenosum (1–2%), psoriasis (10%) and secondary generalized amyloidosis (6%). Extraintestinal CD is one of the specific skin manifestations. It is very rare, poorly known, infrequently described, can present various morphology (papules, nodules, infiltrations, ulcers), and it can be found in different locations. In histopathology extraintestinal CD appears as noncaseating granulomas of the skin and subcutaneous tissue, which are not spreading directly from the alimentary tract.